Efficient Robotic System Design and Utilization Strategies: A focus on logistics center case study (aSSIST Business Review, 2026)
This study proposes efficient design and utilization strategies for robotic systems—one of the core technologies in logistics automation—in response to the sharp increase in logistics volumes and worsening labor shortages in warehouse operations following the surge in online shopping after the COVID-19 pandemic. The theoretical background covers an overview of logistics systems, changes in warehouse types and trends, AI-powered logistics technologies, and the characteristics of key logistics robots such as AGVs, AMRs, ASRS, and handling robots. Subsequently, case analyses compare successful and unsuccessful implementations in domestic and international logistics centers to examine both the effectiveness and limitations of robotic adoption. Strategic recommendations include vendor verification, POC-based validation, ROIdriven cost-effectiveness analysis, and a phased framework for robot deployment. Robotic systems can enhance productivity and operational efficiency while reducing the burden of repetitive and hazardous tasks and supporting human workers, and also suggest the potential for designing and utilizing robotic systems optimized to improve warehouse working environments.
Keywords: Logistics robots; AGV(Automated Guided Vehicle); AMR(Autonomous Mobile Robot); ASRS(Automated Storage and Retrieval System); Handling robots; Artificial Intelligence(AI)